2010
DOI: 10.1002/hbm.21085
|View full text |Cite
|
Sign up to set email alerts
|

Altered intrinsic functional connectivity of anterior and posterior insula regions in high-functioning participants with autism spectrum disorder

Abstract: Impaired understanding of others' sensations and emotions as well as abnormal experience of their own emotions and sensations is frequently reported in individuals with Autism Spectrum Disorder (ASD). It is hypothesized that these abnormalities are based on altered connectivity within "shared" neural networks involved in emotional awareness of self and others. The insula is considered a central brain region in a network underlying these functions, being located at the transition of information about bodily aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
180
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(201 citation statements)
references
References 97 publications
17
180
4
Order By: Relevance
“…Recently, we demonstrated that SCR was positively correlated with AIC activation in the HC group during rest, while no such correlation was found in the ASD group (Eilam-Stock, et al, 2014). In addition, AIC functional connectivity was abnormal in the ASD participants (Eilam-Stock, et al, 2014), which is in agreement with findings from other studies demonstrating abnormal activity and connectivity of the AIC in individuals with ASD (Di Martino A, K Ross, et al 2009; Uddin LQ and V Menon 2009; Ebisch SJ et al 2011). Functional connectivity during task states, especially directed or effective connectivity during socio-emotional tasks, is under-investigated (Uddin and Menon, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Recently, we demonstrated that SCR was positively correlated with AIC activation in the HC group during rest, while no such correlation was found in the ASD group (Eilam-Stock, et al, 2014). In addition, AIC functional connectivity was abnormal in the ASD participants (Eilam-Stock, et al, 2014), which is in agreement with findings from other studies demonstrating abnormal activity and connectivity of the AIC in individuals with ASD (Di Martino A, K Ross, et al 2009; Uddin LQ and V Menon 2009; Ebisch SJ et al 2011). Functional connectivity during task states, especially directed or effective connectivity during socio-emotional tasks, is under-investigated (Uddin and Menon, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…A handful of studies have directly examined functional connectivity of the AIC in ASD (Ebisch, et al, 2011; Eilam-Stock, et al, 2014; Price, et al, 2008). Recently, we demonstrated that SCR was positively correlated with AIC activation in the HC group during rest, while no such correlation was found in the ASD group (Eilam-Stock, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The SMH provides a neural explanation for how emotions regulate decision making under ambiguity which precedes explicit insight, through somatic states which guide social behaviour (Damasio et al, 1996). Recent research has demonstrated alterations in intrinsic functional connectivity within neural networks involved in emotional and interoceptive awareness in ASD (Ebisch et al, 2011). The researchers suggest that in light of the SMH and early theories of emotion, these functional abnormalities may be partly responsible for altered emotional experiences and impaired social abilities in ASD.…”
Section: Theoretical Models Of Social Cognitionmentioning
confidence: 99%
“…13,[20][21][22] Reduced SN RS connectivity has been found in children, adolescents and adults with ASD, affecting connectivity within the SN as well as connectivity between SN key nodes and sensory, prefrontal, and emotion processing regions. 19,[22][23][24][25][26][27] Moreover, increased connectivity within the SN and between the insula and striatal/retrosplenial regions has been reported in children with ASD. 13,21,28 Age effects on connectivity involving both DMN and SN core regions have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%